Pemasaran Usaha Sangcok (Pisang Coklat) Dalam Perspektif Islam - Syariah Hafizhoh; Ananda Sholih; Arif Rio; Audy Ayuni; Delvina Sari; Dewi Aryanti; Nadila Aulia; Rini Amelia (Journal of Creative Student Research, 2023)
Bananas are easily damaged so their durability is very limited. By processing bananas into sangcok it is quite profitable, so that it is used as a side business by the community as an additional income. This study aims to (1) analyze the characteristics of entrepreneurs and business profiles of sangcok (2) availability of raw materials, production technology, use of inputs, costs, income, efficiency and added value of the sangcok agro-industry. The raw material for making sangcok is kepok bananas. Entrepreneurs obtain raw materials for bananas by buying them directly at the market. The results of this study are the marketing plan implemented by the sangcok business, namely in terms of products, always maintain good product quality and the materials used are also halal, the prices applied are also affordable according to what was ordered, a less strategic place does not discourage culinary lovers from continuing to buy sangcok, and promotion strategies are carried out through online and offline media, promoting more through online media, although in doing promotions, honesty is emphasized and not badmouthing other businesses. The conclusion from this study is that the marketing plan carried out in the sangcok business is in accordance with an Islamic perspective. Related marketing plans such as product, price, promotion and place are also based on the Koran, hadith and the practice of the Prophet Muhammad in conducting marketing.